2022
DOI: 10.1021/acsami.2c11530
|View full text |Cite
|
Sign up to set email alerts
|

Large Thermal Conductivity Switching in Ferroelectrics by Electric Field-Triggered Crystal Symmetry Engineering

Abstract: A convenient, reversible, fast, and wide-range switching of thermal conductivity is desired for efficient heat energy management. However, traditional methods, such as temperature-induced phase transition and chemical doping, have many limitations, e.g., the lack of continuous tunability over a wide temperature range and low switching speed. In this work, a strategy of electric field-driven crystal symmetry engineering to efficiently modulate thermal conductivity is reported with first-principles calculations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 65 publications
(108 reference statements)
1
13
0
Order By: Relevance
“…Actually, studies have shown that symmetry breaking can significantly reduce the phonon degeneracy and enhance the avoid-crossing behavior of phonon branches, which results in an increase in the phonon-phonon scattering phase space to limit lattice heat transport. 26,27 The optimized lattice constants are 3.28 Å and 4.12 Å for b-P and b-Sb, respectively, which are in good agreement with the previous work. 28,29 The calculated band structures are shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…Actually, studies have shown that symmetry breaking can significantly reduce the phonon degeneracy and enhance the avoid-crossing behavior of phonon branches, which results in an increase in the phonon-phonon scattering phase space to limit lattice heat transport. 26,27 The optimized lattice constants are 3.28 Å and 4.12 Å for b-P and b-Sb, respectively, which are in good agreement with the previous work. 28,29 The calculated band structures are shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…The switching of electrical polarization is usually driven by the external forces, for example an external electric field. 3,[9][10][11] The experimentally controllable sliding on bilayer h-BN, breaking the lattice symmetry, implies a high potential of modulation of lattice thermal conductivity in such an exotic low-dimensional system.…”
Section: Introductionmentioning
confidence: 99%
“…As an excellent reversible nondestructive thermal transport regulation method, electric field has great potential to be used for realizing thermal switches, which has been verified in the fluid-based thermal diodes 41,42 . However, researches on the solid-state thermal switches driven by the electric field are rare, and are mainly limited in ferroelectric materials [43][44][45] , where the "on" and "off" states In this work, we systematically studied the thermal transport properties of Janus monolayer MoSSe with external electric field applied. It is shown that the thermal transport in Janus monolayer MoSSe exhibits significant adjustability that the thermal conductivity reaches 2.13 times the pristine value under an electric field of 0.040 VÅ −1 applied from S to Se atom.…”
Section: Introductionmentioning
confidence: 99%